Soil and Water Assessment Tool (SWAT) model for hydrological response analysis in the Gajahwong subwatershed, Yogyakarta, Indonesia - Hermawan, Sekar Gading; Suprayogi, Slamet; Fadlillah, Lintang Nur (Brawijaya University, 2025)
Hydrological response is a specific reaction of a watershed to rainfall, and one form is surface runoff, which can be influenced by climatic and physiographic factors. These factors are represented by various parameters that have their own impact on surface runoff, otherwise known as parameter sensitivity. The purpose of this study was to identify the hydrological response in the form of flow discharge based on the application of the Soil and Water Assessment Tool (SWAT) model and to identify the sensitivity of parameters that affect the hydrological response in the Gajahwong subwatershed. The data used in this study came from secondary data obtained from relevant agencies and primary data collected through sampling and laboratory testing. Flow discharge modeling was carried out using SWAT+ software, and the modeling results were automatically calibrated and validated using statistical tests. Meanwhile, sensitivity analysis was conducted by calculating the relative sensitivity values. The results showed that the flow discharge modeling of the Gajahwong subwatershed exhibited a pattern that is similar to the observed discharge. Based on this finding and the validation results with statistical tests, it can be said that the SWAT model can model and predict the flow discharge in the watershed quite well. The input parameter that is very sensitive and has a significant influence on the hydrological response in the subwatershed is the curve number (cn2), with a relative sensitivity value of 1.12.